THE EMBODIED TERRITORY AS THERAPY: EXPLORING PERCEPTIONS THROUGH DANCE AMONG CHILDREN FROM DISPLACED FAMILIES - Andrés Felipe Cuéllar Martínez; Edier Hernán Bustos Velazco; Jaime Duván Reyes Roncancio (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
his article presents the results of an investigation on dance as therapy for early childhood children, considering the body as territory, in two educational institutions in Bogota, D.C. The study seeks to understand the children's experiences and perceptions of their bodies and their environment. It uses dance as a learning tool, adapting the Territorii Method to explore real, lived and thought concepts of territory, where dance therapy occupies a place in their experiences. The research employs a qualitative ethnographic methodology, using field diaries, body mapping and recordings. We developed a pedagogical project focused on folkloric dances. The analyses reveal the emerging category "body as possible territory", which enhances the understanding of howchildren experience their bodies in the context of dance, as well as some implications of dance therapy in processes associated with the relationship between well-being and health.